The Importance Of Words With A Limited Scope Of Use In Increasing The Effectiveness Of Speech (Texas Journal of Philology, Culture and History, 2025)
This article discusses the concept of proverbs, winged words in the speech process and their difference from other units. Such lexemes in speech also perform an important methodological function. If archaism is used in artistic or popular works to give the speech a sense of irony and satire, then historical lexemes are used to vividly express the reality of the past.